2011
DOI: 10.1007/s10620-011-1694-y
|View full text |Cite
|
Sign up to set email alerts
|

Thoraco-Abdominal Pressure Gradients During the Phases of Respiration Contribute to Gastroesophageal Reflux Disease

Abstract: The gastroesophageal barrier function of the LES can be overcome during times when the inspiratory thoraco-abdominal pressure gradient is increased, leading to reflux of gastric juice into the esophagus. This implies that exaggerated ventilatory effort, as occurs with exercise or in respiratory disease, can result in gastroesophageal reflux.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
35
0
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(38 citation statements)
references
References 16 publications
1
35
0
2
Order By: Relevance
“…For example, mean puff volume in hookah smoking is generally over 500 mL [33], [43], [44], which is several times bigger than usual puff volumes in cigarette smoking (40–70 mL) [43]. Therefore, hookah smoking can induce strong negative intra-thoracic pressure and increase thoraco-abdominal pressure gradient, which may increase gastroesophageal reflux [45].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, mean puff volume in hookah smoking is generally over 500 mL [33], [43], [44], which is several times bigger than usual puff volumes in cigarette smoking (40–70 mL) [43]. Therefore, hookah smoking can induce strong negative intra-thoracic pressure and increase thoraco-abdominal pressure gradient, which may increase gastroesophageal reflux [45].…”
Section: Discussionmentioning
confidence: 99%
“…Increased intra-abdominal pressure or thoraco-abdominal pressure gradients may be among the main possible explanations for the association of GERD with BMI and, in particular, central obesity [45], [75]. However, there seems to be other mechanisms contributing to this association, including reduced lower esophageal sphincter pressure in obese individuals [75], [76].…”
Section: Discussionmentioning
confidence: 99%
“…As clinical symptoms have been shown to be unreliable in evaluating GER in IPF patients, GER might contribute to the natural history of IPF through silent microaspiration even in the absence of typical esophageal symptoms . On the other hand, pulmonary fibrosis and worsening lung function may lead to increased negative intrathoracic pressure and greater transdiaphragmatic pressure gradient during respiration, thereby predisposing to gastric reflux in this patient population …”
Section: Introductionmentioning
confidence: 99%
“…14 On the other hand, pulmonary fibrosis and worsening lung function may lead to increased negative intrathoracic pressure and greater transdiaphragmatic pressure gradient during respiration, thereby predisposing to gastric reflux in this patient population. 1,15 While proton-pump inhibitor (PPI) therapy is widely used for symptomatic GER, the effect of acid suppression on pulmonary outcomes in IPF patients has not been definitively established, although a few studies have shown some benefits. 13,16 Studies evaluating broncho-alveolar lavage of patients with IPF demonstrated an increase in both pepsin and bile acids, 14,17,18 suggesting that non-acid reflux may also play a role in the pathogenesis or progression of IPF.…”
Section: Introductionmentioning
confidence: 99%
“…Together with the restricted expiration in asthmatics, there is an increase in abdominal wall muscle contraction to compensate for breathing, lung hyperinflation with lowering of the diaphragm, together with fluctuations in intra-thoracic and intra-abdominal pressures. All the aforementioned might hypothetically explain the significantly higher prevalence of dysphonia, phonatory effort and vocal fatigue in the asthmatic group [24].…”
Section: Discussionmentioning
confidence: 98%